2021
DOI: 10.3947/ic.2021.0067
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Intestinal Protozoan Infections among Children in Southwest Sumba Based on the Type of Water Sources

Abstract: Background Intestinal protozoan infection is a public health problem in Indonesia, particularly in regions lacking clean water sources such as Perokonda and Perobatang villages, Southwest Sumba Regency, East Nusa Tenggara Province. The residents of Perokonda and Perobatang villages use wells and unprotected open springs respectively. Therefore, this study aims to determine the prevalence of intestinal protozoan infections in these two villages. Materials and Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
0
0
1
Order By: Relevance
“…A drinking holder with an open container made of cement is placed in the cage, allowing contamination of the drinking water which is a factor causing cryptosporidiosis (waterborne disease). This is in accordance with the statement of Wahdini et al (2021), who stated that poor water quality contributed to the high prevalence of digestive protozoan infections. Meanwhile, Osman et al (2016) reported that consumption of untreated water tripled the risk of protozoal infection compared to water treated with chlorite.…”
Section: Resultssupporting
confidence: 92%
“…A drinking holder with an open container made of cement is placed in the cage, allowing contamination of the drinking water which is a factor causing cryptosporidiosis (waterborne disease). This is in accordance with the statement of Wahdini et al (2021), who stated that poor water quality contributed to the high prevalence of digestive protozoan infections. Meanwhile, Osman et al (2016) reported that consumption of untreated water tripled the risk of protozoal infection compared to water treated with chlorite.…”
Section: Resultssupporting
confidence: 92%
“…The prevalence rate of giardiasis compared to the previous study in Southwest Sumba, Indonesia, was lower (19%). 23 Albendazole single dose 400 mg is effective for treating STH infections but is less effective for protozoa infection. The suggested albendazole dosage for giardiasis for children is 10 mg/kg daily for five days.…”
Section: Discussionmentioning
confidence: 99%
“…Di Nusa Tenggara Timur didapatkan prevalensi protozoa usus pada anak sebesar 20%. 10,11 Di Sumatera barat, penelitian tentang angka kejadian infeksi protozoa usus pada anak masih sedikit, Penelitian yang telah dilakukan di rumah singgah "Amanah" kota Padang didapatkan prevalensi protozoa usus pada anak-anak sebesar 40,91% dan penelitian yang dilakukan di SD Negeri 15 Ulu Gadut, Padang di dapatkan angka infeksi protozoa usus sebesar 43,36%. 4,12 Penelitian lainnya yang dilakukan di SD Negeri 02 dan SD Negeri 12 Ulakan Tapakis Kabupaten Padang Pariaman dari 83 orang di dapatkan prevalensi protozoa intestinal sebanyak 14 (16,9%).…”
Section: Pendahuluanunclassified